Spatial Analysis of Startup User Locations and Its Accuracy Values Using Spatial Data Modeling, Palembang City, Indonesia - Monanisa, Monanisa (2022)
Increasingly thriving businesses that utilize existing startups are a form of disruptive innovation. Today, these startup users can multiply the number of their customers online to include a broader population in downtown areas. This research aimed to analyze the locations of startup users in Palembang City, Indonesia, spatially using the Accuracy Values of Spatial Data Modeling. Frequency, a descriptive quantitative approach, and spatial data modeling analysis were the two methods applied to 364 sampling points distributed in Palembang City. The results indicated that single women with an average of high school or equivalent education dominated the demographics of the startup users. Also, on average, the startup users were 20-29 years of age. The spatial analysis revealed that their business locations formed a dispersed pattern, with an even density in the downtown area. Based on the sensitivity and specificity values on the ROC curve (receiver operating characteristic) and the accuracy level obtained from AUC (area under the ROC curve), the Spatial Data Modeling (SDM) of the density distribution showed very high-accuracy results, 98.8. © 2022 Faculty of Geography UGM and The Indonesian Geographers Association © 2022 by the authors. Licensee Indonesian Journal of Geography, Indonesia.